Research Progress and Functional Applications of Food Protein Fibrils - Zhenling LANG; Jie ZHUANG; Hongzheng LU; Shaoxiao ZENG; Haoran CHEN (Shipin gongye ke-ji)
Recently, protein fibrillization has attracted widespread attention due to its ability to endow food with good functional properties and better stability. Protein fibrils, a kind of food raw material with wide application prospect, can be self-assembled under proper external conditions. To comprehensively understand food protein fibers, this paper provides a review of research progress in the self-assembly, structural characteristics, sources, and functional properties of food protein fibers. The fibrillation conditions of protein fibers, the mechanism of self-assembly, the functional properties (including physicochemical properties and biological activity), and applications in the food industry are emphasized. Finally, building upon existing research, this review innovatively provides new insight into the research trends of protein fibrils, aiming to provide reference for their high-quality application in the food industry.